Dietary Melatonin Protects Against Behavioural, Metabolic, Oxidative, and Organ Morphological Changes in Mice that are Fed High-Fat, High-Sugar Diet - Onaolapo, Adejoke Y.; Adebisi, Ebenezer Oladimeji; Adeleye, Adegbayi Emmanuel; Olofinnade, Anthony Tope; Onaolapo, Olakunle James (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2020)
Background: Metabolic syndrome is a complex pattern of disorders that occur jointly and is associated with an increased risk of cardiovascular and cerebrovascular disease. Therefore the need for more-efficient options of treatment has become imperative. Objective: This study examined the effect of dietary-melatonin in the management of behavioural, metabolic, antioxidant, and organ changes due to high-fat/high-sugar (HFHS) diet-induced metabolic syndrome in mice. Methods: Mice were randomly assigned into five groups of ten animals each. Groups were normal control [fed standard diet (SD)], HFHS control, and 3 groups of melatonin incorporated into HFHS at 2.5, 5, and 10 mg/kg of feed. Mice were fed for seven weeks, and body weight was assessed weekly. Open-field behaviours, radial-arm, and Y-maze spatial memory were scored at the end of the experimental period. Twenty-four hours after the last behavioural test, blood was taken for estimation of blood glucose levels after an overnight fast. Animals were then euthanised, and blood was taken for estimation of plasma insulin, leptin, and adiponectin levels, and serum lipid profile. The liver, kidneys, and brain were excised and processed for general histology, while homogenates of the liver and whole brain were used to assess oxidative stress parameters. Results: Results showed that dietary melatonin (compared to HFHS diet) was associated with a decrease in body weight, food intake, and novelty-induced behaviours; and an increase in spatial-working memory scores. A decrease in glucose, insulin, leptin, and malondialdehyde levels; and an increase in adiponectin levels and superoxide dismutase activity were also observed. Histomorphological/ histomorphometric examination revealed evidence of organ injury with HFHS diet, and varying degrees of amelioration with melatonin-supplemented diet. Conclusion: In conclusion, dietary melatonin supplementation may have beneficial effects in the management of the metabolic syndrome.
Keywords: glucose